2008
DOI: 10.1152/ajpheart.00690.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone protects the myocardium against ischemia-reperfusion injury in eNOS and iNOS knockout mice

Abstract: Ye Y, Lin Y, Manickavasagam S, Perez-Polo JR, Tieu BC, Birnbaum Y. Pioglitazone protects the myocardium against ischemia-reperfusion injury in eNOS and iNOS knockout mice. Am J Physiol Heart Circ Physiol 295: H2436 -H2446, 2008. First published October 17, 2008 doi:10.1152/ajpheart.00690.2008.-Endothelial nitric oxide synthase (eNOS) activation with subsequent inducible NOS (iNOS), cytosolic phospholipase A2 (cPLA2), and cyclooxygenase-2 (COX2) activation is essential to statin inhibition of myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 74 publications
2
43
1
Order By: Relevance
“…Neilan et al (25) reported that genetic disruption of COX-2 increases cardiac dysfunction after treatment with doxorubicin due to an increase in apoptosis of cardiac cells, suggesting that COX-2 and prostacyclin modulate the expression of genes encoding for proteins involved in apoptosis. Ye et al (26) reported that the myocardial protective effect of PIO is iNOS-independent and may be only partially dependent on eNOS. Up-regulation of COX-2 by PIO is independent of NOS (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neilan et al (25) reported that genetic disruption of COX-2 increases cardiac dysfunction after treatment with doxorubicin due to an increase in apoptosis of cardiac cells, suggesting that COX-2 and prostacyclin modulate the expression of genes encoding for proteins involved in apoptosis. Ye et al (26) reported that the myocardial protective effect of PIO is iNOS-independent and may be only partially dependent on eNOS. Up-regulation of COX-2 by PIO is independent of NOS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al (26) reported that the myocardial protective effect of PIO is iNOS-independent and may be only partially dependent on eNOS. Up-regulation of COX-2 by PIO is independent of NOS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the newer antidiabetic agents have also been reported to limit infarct size in the diabetic and nondiabetic heart, including 1) thiazolidinediones, such as rosiglitazone (Morrison et al, 2011;Palee et al, 2013) and pioglitazone (Ye et al, 2008;; 2) GLP-1 analogs, such as liraglutide (Noyan-Ashraf et al, 2009) and exenatide (Timmers et al, 2009); and 3) dipeptidyl peptidase-4 inhibitors, such as sitagliptin (Sauve et al, 2010;Ye et al, 2010a;Hausenloy et al, 2013b) and vildagliptin . The novel antidiabetic agent mitiglinide (Ogawa et al, 2007) has been found to affect the efficacy of preconditioning or postconditioning in the diabetic heart.…”
Section: Antidiabetic Therapymentioning
confidence: 99%
“…[202][203][204] Calcium antagonist pretreatment is associated with cardioprotection, 205 but calcium antagonists seem not to interfere with conditioning. 206 In antidiabetic treatment, there are the sulfonylureas that interfere with cardioprotective signaling because they inhibit ATP-dependent potassium channel activation, 187,207 whereas some glitazones, 208,209 the glucagonlike peptide 1 analog exenatide, [210][211][212] and some dipeptidyl peptidase 4 inhibitors 213,214 protect per se. Only high-dose aspirin that blocks both cyclo-oxygenase 1 and 2 seems to interfere with cardioprotection.…”
Section: Lack Of Comorbidities and Comedications In Animal Experimentsmentioning
confidence: 99%